SCHOOL TEXTBOOKS OF NATIONAL HISTORY AS AN INSTRUMENT OF THE MEMORY POLICY OF THE SOVIET STATE - Isabella S. Ogonovskaya (Sovremennye Issledovaniâ Socialʹnyh Problem, 2024)
Background. The problem of the influence of state policy on the development of historical education in the Soviet school, as well as the content of school textbooks on the history of the USSR, is updated. The reasons for the transformation of school historical education in accordance with changes in political attitudes, stages of development of Soviet society, the change of leaders of the country, conceptual approaches in historical science are considered.